Changes in physical properties of growing media constituents according to biodegradation - Durand, Stan; Michel, Jean-Charles (Frontiers in Horticulture, 2026)
The use and exploration of more sustainable materials for growing media, in response to the search for alternatives to peat, are expanding. Many locally available organic resources are currently under study for this purpose. However, their biological stability remains a major limitation. Understanding the effect of biodegradation on the physical properties of these materials, in order to assess their long-term suitability for ensuring water supply and root system respiration, remains largely unexplored. The objectives of this research were to evaluate the biological stability of various organic materials over a 6-week biodegradation process; to investigate how biodegradation alters key physical properties; and to determine whether these alterations stem from changes in particle size distribution. Initial and post-biodegradation physical properties and particle size distribution were analyzed. Biodegradation was measured via respirometry. The protocol employed aerobic conditions, fertilizer addition, and a temperature of 35°C to reach a substantial biodegradation rate. As a result, the methodology employed led to biodegradation rates comparable to, or exceeding, those reported in the literature. No significant changes were observed in particle size distribution after biodegradation, probably due to overall low biodegradation rates coupled with heterogeneous particle sizes. No significant changes were observed in total porosity or available water either. The significant changes observed were a decrease in air-filled porosity, resulting from a general increase in water retention properties at suctions of −10 cm and above. These observations therefore suggest the hypothesis of a change in the integrity of the particle surface, with the formation of fine pores, rather than fragmentation leading to changes in particle size and organization. These observations highlight the importance of assessing changes in physical properties during relatively long biodegradation processes for potentially biologically unstable raw materials, in order to adapt agronomic practices to the changing properties of the materials.